Spiritual Concert “Glory Be to This Day” of S. A. Degtyarev: Compositional and Stylistic Features of Choral Writing - Romenskaya, Lyudmila; Golovin, Aleksandr; Kurganskiy, Sergey; Bezuglova, Olga (Journal of History Culture and Art Research, 2018)
This article analyzes the genre of spiritual concert of S.A. Degtyarev “Glory be to this day” in the context of the style of the Russian choral writing of the late XVIII – early XIX centuries. Compositional, genre, dramatic patterns, the technological specifics of the structure of the choral works presented as elements of meaning of music, by means of which the transition of the language of space the artistic content. The study of the creative heritage of S.A. Degtyarev as one of the founders of the domestic choral concert seems to be an interest of modern musicology. The category “choral letter” is considered by the authors as a carrier of historical, cultural and ideological traditions. The specificity of the musical stylistics of the analyzed concert is based on the combination of Baroque music traditions (rhetorical writing techniques, imitation polyphony technique), classical style (the use of the principle of “contrast in unity” at the level of architectonics of the artistic space, homophone-harmonic structure of the musical language) and part-time multi-part concert. The principle of functional variability of textural layers is revealed through the differentiation of choral parties, coloring tessitore-tone areas such as media music concept. The analysis of the composition-dramatic structure, sound-acoustic realization of the choral parts of the concert allows to reveal the specifics of the style of S.A. Degtyarev's choral writing.